The Employability of Persons with Disabilities and Groups at Risk in Enterprises of Skills Development: International Perspective of Convention on the Rights of Persons with Disabilities (CRPD) - Turmusani, Majid (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change)

(untitled) (Réseau International sur le Processus de Production du Handicap, 2012)
This account explores the employability of Persons with Disabilities (PWDs) in enterprises of skills development in eleven countries (Canada, Brazil, Spain, Italy, Switzerland, Belgium, Luxembourg, Slovakia, Romania, Uganda and Afghanistan). Participatory research approach is used including empirical component in Canada, aspiring to inform labour market policies, namely access/accessibility and safety nets. Results show that enterprises (N=39) are somehow serving PWDs, but they do not have special provisions to reinforce disability focused services. Particularly, there are inadequate disability policies and a limited presence of disabled people in programs. This is possibly due to limited workplace accommodations, limited capacity and lack of resources. The research calls for an activation of Convention on the Rights of Persons with Disabilities (CRPD) into the sector of enterprises, coupled with capacity building in disability policy research and after placement services. In essence, this means: increasing employability opportunities; reducing vulnerability through social protection and reinforcing the capacity of enterprises.